2017
DOI: 10.1093/gigascience/gix039
|View full text |Cite
|
Sign up to set email alerts
|

The draft genome of blunt snout bream (Megalobrama amblycephala) reveals the development of intermuscular bone and adaptation to herbivorous diet

Abstract: The blunt snout bream Megalobrama amblycephala is the economically most important cyprinid fish species. As an herbivore, it can be grown by eco-friendly and resource-conserving aquaculture. However, the large number of intermuscular bones in the trunk musculature is adverse to fish meat processing and consumption. As a first towards optimizing this aquatic livestock, we present a 1.116-Gb draft genome of M. amblycephala, with 779.54 Mb anchored on 24 linkage groups. Integrating spatiotemporal transcriptome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 88 publications
4
50
0
1
Order By: Relevance
“…The GC percentage (36%) found in this study is similar to that of the genomes of other cyprinids ( Supplementary Table 6). The overall percentage of repeat elements observed was similar to the repeat contents of the cavefish Sinocyclocheilus grahami (Yang et al, 2016) and grass carp Ctenopharyngodon idellus (Wang et al, 2015), higher than common carp Cyprinus carpio (Xu P. et al, 2014) and blunt snout bream Megalobrama amblycephala (Liu et al, 2017) but lower than zebrafish Danio rerio (Howe et al, 2013) (Supplementary Table 6). The most abundant repeat elements in the rohu genome were found to be DNA transposons, accounting for 33.58% of the classified elements, followed by retrotransposons (6.1%), LINEs (3.5%), and SINEs (0.8%), as observed in other carp genomes.…”
Section: Genome Organizationsupporting
confidence: 62%
“…The GC percentage (36%) found in this study is similar to that of the genomes of other cyprinids ( Supplementary Table 6). The overall percentage of repeat elements observed was similar to the repeat contents of the cavefish Sinocyclocheilus grahami (Yang et al, 2016) and grass carp Ctenopharyngodon idellus (Wang et al, 2015), higher than common carp Cyprinus carpio (Xu P. et al, 2014) and blunt snout bream Megalobrama amblycephala (Liu et al, 2017) but lower than zebrafish Danio rerio (Howe et al, 2013) (Supplementary Table 6). The most abundant repeat elements in the rohu genome were found to be DNA transposons, accounting for 33.58% of the classified elements, followed by retrotransposons (6.1%), LINEs (3.5%), and SINEs (0.8%), as observed in other carp genomes.…”
Section: Genome Organizationsupporting
confidence: 62%
“…Duplication of T1R2 genes of stickleback, resulting in enhanced perception for substances important for survival and reproduction, has been suggested as an adaptive strategy to varied environment [28]. In the present study, we observed that high T1R2 duplications in grass carp (six copies) as well as blunt snout bream are related to the vegetarian adaptation through the comparative analysis in cyprinid evolution [29].…”
Section: Discussionsupporting
confidence: 53%
“…The high-quality reads were BLAST searched against the CC genome and BSB genome by applying BWA software with default options (Li and Durbin, 2009). For the genome comparison of RCC-L and GF-L, the RCC-L and the GF-L genome sequences were modelled as sequencing data with 90× read depth and aligned to the CC, BSB, and RCC genomes (Xu et al, 2014;Liu et al, 2016;Liu et al, 2017).…”
Section: Mapping and Identities Using Genome Resequencingmentioning
confidence: 99%